PERANCANGAN BRAND CAMPAIGN DAN MEDIA PROMOSI UNTUK MENINGKATKAN AWARENESS VALUE BRAND ONY POTTERY - Liony Suryaputra; Paulina Tjandrawibawa (Universitas Ciputra Surabaya, 2021)
This study aims to introduce Ony Pottery to consumers with a brand campaign and the use of social media as a promotional media. Ony Pottery is a ceramic brand based in Surabaya. The research method used in this research is descriptive qualitative. The subjects of this study were consumers and followers of Ony Pottery on social media. The use of social media as a promotional medium is the right thing in this Covid19 pandemic. Ony Pottery's brand value is still conveyed to consumers through social media. Modernism is a design style raised by Ony Pottery in terms of products, social media to promotional strategies. It is hoped that by using the increased awareness, the public will get to know the ceramic brand Ony Pottery. Keywords: Authentic, Selfmade, Clay, Pottery, Brand Campaign